Theory and Applications of Smart Cameras - Kyung, Chong-Min.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This book presents an overview of smart camera systems, considering practical applications but also reviewing fundamental aspects of the underlying technology.  It introduces in a tutorial style the principles of sensing and signal processing, and also describes topics such as wireless connection to the Internet of Things (IoT) which is expected to be the biggest market for smart cameras. It is an excellent guide to the fundamental of smart camera technology, and the chapters complement each other well as the authors have worked as a team under the auspice of GFP(Global Frontier Project), the largest-scale funded research in Korea.  This is the third of three books based on the Integrated Smart Sensors research project, which describe the development of innovative devices, circuits, and system-level enabling technologies.  The aim of the project was to develop common platforms on which various devices and sensors can be loaded, and to create systems offering significant improvements in information processing speed, energy usage, and size. This book contains extensive reference lists, introduces the reader to the subject in a tutorial style and also reviews state-of-the-art results, which allows it to be used as a guide for starting researchers.  .
PART 1 Fundamental/Energy-related Issues of Smart Cameras -- 1 CMOS Image Sensor for Smart Cameras; Jongho Park -- 2 Architectural Analysis of a baseline ISP pipeline; Hyun Sang Park -- 3 An Ultra-Low-Power Image Signal Processor for Smart Camera Applications; Zhenhong Liu, Nam Sung Kim -- 4 Foundations and Applications of 3D Imaging; Min H. Kim -- 5 E-R-D Optimization in video compression; Hyuk-Jae Lee, Hyun Kim, Chae-Eun Rhee -- PART 2 Event/Object Detectors for Smart Sensing -- 6 Low-Power Operation for Video Event Data Recorder; Jinyoung Yang, Jongpil Jung -- 7 Low Power Face Detection for Smart Camera; Hyung-Il Kim, Seung Ho Lee, Yong Man Ro -- 8 Accurate Face and Human Detection Using Hybrid Local Transform Features; Daijin Kim, Bongjin Jun -- 9 Adaptive Resource Management for Sensor Fusion in Visual Tracking; Bohyung Han, Seong-Wook Joo, Larry S. Davis -- 10 Traffic Pattern Analysis and Anomaly Detection via Probabilistic Inference Model; Hawook Jeong, Youngjoon Yoo, Kwang Moo Yi, Jin Young Choi -- 11 Event Detection Module for Low Power Camera; Byung-geun Lee, Moongu Jeon -- 12 Advanced Human Detection Using Fused information of Depth and Intensity Images; Gyu-Hong Lee, Dong-Suk Kim and Chong-Min Kyung -- PART 3 Wireless Connectivity for Video Sensor Networks -- 13 Time Synchronization for Multi-hop Surveillance Camera Systems; Hyuntae Cho -- 14 Distributed Medium Access for Camera Sensor Networks: Theory and Practice; Hojin Lee, Donggyu Yun, Yung Yi -- 15 Wireless Sensor Network for Video Sensors; HyungWon Kim.
Keywords: Telecommunication; Lasers; Image processing -- Digital techniques; Computer vision; Microwaves, RF Engineering and Optical Communications; Laser; Computer Imaging, Vision, Pattern Recognition and Graphics